The essential controller : an introduction to what every financial manager must know - Bragg, Steven M. (J. Wiley & Sons, 2012)
"This book is designed to give the new controller a firm foundation in the concepts of managing the accounting department, locating GAAP information, analyzing and knowing what to do with key accounting information, and setting up controls systems that reduce a company's risk of loss. These core areas are essentials to a controller's success. New to this edition will be a discussion of finance strategy; introduction of the accounting standards codification, update of the taxation strategy; and a new controller checklist will be added as an appendix"--